L'informatique juridique : en progression vers un processus d'intelligence artificielle - Goulet, Jean (Les Cahiers de droit, 1980)
This paper deals primarily with computer-assisted legal research. It attempts to sketch the current state of the art, mainly in the United States and Canada, with special reference to systems oriented towards the processing of legislative data. The author suggests a checklist of the main requirements the systems of the 80's will have to answer to, in order to fulfill the growing needs of the new computer-minded generations of law graduates. Along these lines, this paper deals also with the second generation systems dedicated to automated legal research ; these could be expected to show some form, albeit elementary, of humanlike intelligence. Four prototypes of such systems are considered; they are the American Bar Foundation's and Jeffrey Meldman's systems, as well as the well-known JUDITH and TAXMAN systems. The paper concludes on a glimpse of the Third Wave of computerized legal research, in the belief that the legal profession will meet the challenge of the computer age, will learn to live and work with this new technology, and will master the artificial but sometimes acute intelligence of our new friend, the Robot.